Some Aspects of S. Šalkauskis’ Life and Activity - Gaidamavičienė, Irena (Problemos, 1988)
The article deals with the life and activity of the Lithuanian philosopher S. Šalkauskis (1886-1941). The theoretical heritage of the philosopher is considered only in some points. The author of the article mainly attempts to demonstrate the scope and significance of S. Šalkauskis’ activity.